Endometrial cancer surveillance adherence reduces utilization and subsequent costs - Schwartz, Zachary P.; Frey, Melissa K.; Philips, Sarah; Curtin, John P. (Gynecologic oncology, 2017)
In June 2011, the SGO recommended that physical exam and symptoms be the primary surveillance methods in patients with endometrial cancer. We sought to evaluate adherence to these guidelines by comparing the use of CT scans, paps and serum CA125 ordered for endometrial cancer surveillance before and after publication of these guidelines. A retrospective review was performed for all patients undergoing surveillance for endometrial cancer at a single institution between June 2009 and June 2013. We assessed the number of patients without symptoms or abnormal physical exam findings who underwent surveillance CT scans, paps and/or CA125 during the 2years pre- and 2years post-SGO guidelines. 92 patients (n=48 pre-6/2011, n=44 post-6/2011) were identified. Mean patient age was 58years. No significant difference in age, ethnicity, body mass index, or disease grade or stage was noted. There was a significant decline in surveillance CT scans (n=13, 27% vs. n=4, 9%, p=0.03), CA125 (n=14, 29% vs. 5, 11%, p=0.035) and paps (n=34, 71% vs. n=8 vs. 18%, p<0.001). There was no significant difference in disease status at the last follow-up. Institutional cost of surveillance also declined ($14,102.46 2years pre-guidelines, $3,054.99 2years post-guidelines). In a single urban academic public hospital, after only 2years, clinical adherence to the 2011 SGO endometrial cancer surveillance guidelines resulted in a significant decline in the use of CT scans, CA125 and paps. This reduction does not appear to affect patient outcomes and led to an appreciable decrease in surveillance costs. •Single institution shows decline in CT's, CA125's, and Paps due to SGO guidelines.•Adherence to SGO guidelines did not negatively impact patient outcomes.•Cost of surveillance care declined secondary to adherence to these SGO guidelines.